2014
DOI: 10.4254/wjh.v6.i5.347
|View full text |Cite
|
Sign up to set email alerts
|

Central hepatectomy for centrally located malignant liver tumors: A systematic review

Abstract: AIM:To study whether central hepatectomy (CH) can achieve similar overall patient survival and disease-free survival rates as conventional major hepatectomies or not. METHODS:A systematic literature search was performed in MEDLINE for articles published from January 1983 to June 2013 to evaluate the evidence for and against CH in the management of central hepatic malignancies and to compare the perioperative variables and outcomes of CH to lobar/extended hemihepatectomy. RESULTS:A total of 895 patients were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 57 publications
(140 reference statements)
5
38
1
5
Order By: Relevance
“…This volume decreases to 40–60% in patients with pre-existing parenchymal disease 20. This finding is consistent with multiple reports stating that ERH and a diminished FLR were significant and independent predictors for PHLF 2122232425. Kauffmann and Fong 21.…”
Section: Discussionsupporting
confidence: 89%
“…This volume decreases to 40–60% in patients with pre-existing parenchymal disease 20. This finding is consistent with multiple reports stating that ERH and a diminished FLR were significant and independent predictors for PHLF 2122232425. Kauffmann and Fong 21.…”
Section: Discussionsupporting
confidence: 89%
“…No significant differences for postoperative morbidity and mortality between CH and extend hepatectomy (EH) were demonstrated by Lee's systematic review 4 . Additionally, a recent case-matched study from the same author showed no differences in 90-day mortality, biliary leaks and postoperative liver failure 4 . Moreover, this study also showed longer length of stay, higher postoperative bilirubin and longer prothrombine time for patients who underwent extend hepatectomy.…”
Section: Discussionmentioning
confidence: 73%
“…However, those concerns were not corroborated in comparative series of CH versus extend hepatectomy 4 . Moreover, CH presented shorter operative time (268 versus 299 min), and lower blood loss (882 vs. 1352 ml) when compared to extend hepatectomy.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although segmental resections have an advantage in terms of tissue preservation, this must be weighed against increased blood loss and a considerable risk of biliary complications. 39,40 Furthermore, these resections are more frequently associated with positive margins and, depending on their location, may lead to inadvertent injury to important portal structures. In the case of a planned staged resection, such an injury may render the second operation impossible.…”
Section: Segmental Resectionsmentioning
confidence: 99%